2017
DOI: 10.1021/acs.jpcb.7b05454
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Malic Acid Natural Deep Eutectic Solvent Nanostructure to Solidification and Hydration

Abstract: Little is presently known about the unique nanostructure of deep eutectic solvents (DES). The order of the liquid-solid phase transition is contended and whether DES-water mixtures are merely aqueous solutions, or have properties dominated by the eutectic pair, is unclear. Here, we unambiguously show the structure of choline chloride-malic acid (malicine) as a liquid, and also in solid and hydrated forms, using neutron total scattering on D/H isotope-substituted samples, and quasi-elastic neutron scattering (Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
144
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(168 citation statements)
references
References 55 publications
17
144
2
2
Order By: Relevance
“…The water content of the DES was determined before and after each experiment by Karl-Fischer titration (Mettler Toledo DL32 Karl-Fischer Coulometer, Aqualine Electrolyte A, Aqualine Catholyte CG A) in order to ensure water presence was kept to a minimum. Those measurements showed that the water content of the solvent was kept below 0.3 wt/% during all the experimental procedures presented here, which we assume to be negligible and have to little impact on the characteristics of the DES [3,4].…”
Section: A Materialsmentioning
confidence: 75%
See 1 more Smart Citation
“…The water content of the DES was determined before and after each experiment by Karl-Fischer titration (Mettler Toledo DL32 Karl-Fischer Coulometer, Aqualine Electrolyte A, Aqualine Catholyte CG A) in order to ensure water presence was kept to a minimum. Those measurements showed that the water content of the solvent was kept below 0.3 wt/% during all the experimental procedures presented here, which we assume to be negligible and have to little impact on the characteristics of the DES [3,4].…”
Section: A Materialsmentioning
confidence: 75%
“…However, the native environment for lipids in-vivo is far from a simple aqueous solution. In fact, it has been suggested [2,4] that DES might form within the crowded cellular environment and could assist in solubilizing biological species in an intermediate environment between that of the hydrophobic phospholipid tails and highly polar water-rich regions, thereby assisting survival under extreme conditions such as freezing temperatures or drought where the water content of cells is restricted. Despite the broad interest in these systems, the presence of stable phospholipid monolayers at the interface between air and an ionic solvent media has not been previously reported, to the best of the authors' knowledge.…”
mentioning
confidence: 99%
“…Both the ''DES-in-water'' and the ''water-in-DES'' with low water contents -e.g., one or two moles of water per mole of DESsystems have been widely studied and agreement exists with regard to their respective natures -e.g., a simple aqueous dilution of the individual DES components in the former case 73,74 or water playing the role of a second small HBD in the latter one. [75][76][77] However, less agreement exists with regard to the nature of intermediate dilutions; this is the ''water-in-DES'' system with high water contents where the water fraction is yet too low to promote the DES rupture and dissolve its components. Interestingly, in a recent work dealing with pseudo-concentrated aqueous solutions of DES composed of resorcinol, urea, and ChCl, we demonstrated that water played the role of an additional HBD or HBA and, hence, was interstitially accommodated within the DES-based 3D H-bonded network, thus forming the ''water-in-DES'' system.…”
Section: Feature Article Chemcommmentioning
confidence: 99%
“…So, making appropriate solutions from the desired DESs and less viscous cosolvents is an easy way out. In this regard, the aqueous solutions of DESs as hybrid green systems have garnered increased attention …”
Section: Introductionmentioning
confidence: 99%